2014
DOI: 10.1108/edi-10-2013-0081
|View full text |Cite
|
Sign up to set email alerts
|

Weight bias in US candidate selection and election

Abstract: Purpose -The purpose of this paper is to use data from the 2008 and 2012 US Senate elections to examine the relationship between candidate size (obese, overweight, normal weight) and candidate selection and election outcomes. Design/methodology/approach -Using pictures captured from candidate web sites, participants rated the size of candidates in the primary and general US Senate elections. w 2 analyses, t-tests and hierarchical multiple regressions were used to test for evidence of bias against overweight an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…This study suggests that people who read these stigmatizing and unflattering remarks are likely to draw unfair conclusions about Christie’s (or any other large politician’s) leadership competence on the basis of negative often demeaning physical descriptions. As Roehling and colleagues (Roehling et al, 2009; Roehling et al, 2014) have shown, large-size politicians rarely make it past the primaries and only if they are male.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study suggests that people who read these stigmatizing and unflattering remarks are likely to draw unfair conclusions about Christie’s (or any other large politician’s) leadership competence on the basis of negative often demeaning physical descriptions. As Roehling and colleagues (Roehling et al, 2009; Roehling et al, 2014) have shown, large-size politicians rarely make it past the primaries and only if they are male.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have recently investigated how a candidate’s weight affects political outcomes. Roehling et al (2014) examined 126 candidate pairs who ran in senatorial elections in 2008 and 2012. They found that all obese and overweight females were eliminated in the primary, and in almost every instance, the thinner male candidate was elected.…”
Section: Obesity and Perceptions Of Competence Of Political Leadershipmentioning
confidence: 99%
“…Re and colleagues 71 show that individuals with faces indicating elevated BMI are rated lower in leadership traits. Similarly, Roehling and coauthors 18 find that obese individuals are less likely to emerge as candidates for political office and, when they do, receive lower absolute vote share and lower relative vote share compared to their more slender opponents. Figure 1 presents silhouettes of average people across a range of BMis controlling for height.…”
Section: K F D"mentioning
confidence: 92%
“…Evidence suggests individuals infer information that predicts election outcomes with as little as one second of exposure to a candidate's image. 3 Researchers have found evaluations of political leaders and election outcomes can be predicted with physical attributes of leaders such as attractiveness, 4 • 5 • 6 • 7 • 8 • 9 "looking the part" (e.g., competence), 3 • 8 • 9 • 10 • 11 votercandidate facial similarity, 12 masculinity-femininity, 13• 14 vocal communications, 15 • 16 • 17 obesity, 18 height, 19 • 20 • 21 sex, 22 • 23 and skin color. 24 Some scholars explain these effects by concluding physical features prime elements of modern leadership prototypes such as competence, intelligence, and leadership skills.…”
mentioning
confidence: 99%
“…The study of language, and particularly metaphor, requires in-depth understanding of a particular phenomenon (Crisp, Heywood, & Steen, 2002). Obese political candidates often experience ridicule and stigmatization that could deter them from continuing to run for political office (Roehling et al, 2014). Christie is a good focus for a case study about political news coverage that stigmatizes obesity.…”
Section: Study Rationalementioning
confidence: 99%